2021
DOI: 10.3389/fped.2021.624116
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: A Novel Pathogenic Missense Mutation in FAS: A Multi-Generational Case Series of Autoimmune Lymphoproliferative Syndrome

Abstract: Autoimmune Lymphoproliferative Syndrome (ALPS), commonly caused by mutations in the FAS gene, is a disease with variable penetrance. Subjects may be asymptomatic, or they may present with lymphadenopathy, splenomegaly, cytopenias, or malignancy. Prompt recognition of ALPS is needed for optimal management. We describe a multi-generational cohort presenting with clinical manifestations of ALPS, and a previously unreported heterozygous missense variant of uncertain significance in FAS (c.758G >T, p.G253V),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…In addition, the coexistence of strongly diminished ADA2 activity with an oligosymptomatic phenotype in the sister can be explained by well-known intrafamilial phenotypic variability despite the same underlying homozygous mutations (11,19,30,(36)(37)(38)(39)(40). However, even if individuals with biallelic ADA2/CECR1 pathogenic variants were reported to have remained asymptomatic until adulthood or to have never developed clinical manifestations of DADA2 (41), the sister of our patient is currently following up with another adult rheumatology center.…”
Section: Discussionmentioning
confidence: 90%
“…In addition, the coexistence of strongly diminished ADA2 activity with an oligosymptomatic phenotype in the sister can be explained by well-known intrafamilial phenotypic variability despite the same underlying homozygous mutations (11,19,30,(36)(37)(38)(39)(40). However, even if individuals with biallelic ADA2/CECR1 pathogenic variants were reported to have remained asymptomatic until adulthood or to have never developed clinical manifestations of DADA2 (41), the sister of our patient is currently following up with another adult rheumatology center.…”
Section: Discussionmentioning
confidence: 90%
“…Hence, a double-hit mechanism (i.e., predisposing germline mutations followed by disease-triggering somatic mutations) has been hypothesized [19]. Moreover, the variable penetrance seen in ALPS patients' pedigrees [20] suggested that a digenic model of inheritance could be applicable, due to a possible role of disease-modifying genes [21]. Finally, variants in FAS and FASL have been reported in patients displaying multifactorial autoimmune diseases and cancer (e.g., systemic lupus erythematosus, SLE) [13,[22][23][24].…”
Section: Requiredmentioning
confidence: 99%
“…ALPS patients' pedigrees often show an incomplete disease penetrance [20,63]. However, additional genetic mechanisms may come into play and ultimately determine the expression of an ALPS disease phenotype [1,17].…”
Section: Double-hit Hypothesis In Alps: One Disease Two Mutations Neededmentioning
confidence: 99%
See 2 more Smart Citations